The New Public Management in Europe - Towards Convergence or Difference? - Wood, Geoffrey (Marketing & Menedzsment, 2019)
This article explores the impact of New Public Management policies and practices within the European Union. It is concluded that the process of public sector reform - and the fuller adoption of the NPM model - is likely to remain contested, characterized by both the persistence of particular public administration traditions, and the emergence of new compromises, reflecting competing pressures and interests.